MANAGEMENT OF THE PERFORMANCE OF WORK OF A MEDICAL INSTITUTION UNDER THE CONDITIONS OF CHANGES - Hrytsko, R.Yu.; Kvasnii, L.G.; Hrytsko, O.M. (The actual problems of regional economy development, 2023)
The article proves the need to find ways to ensure the effectiveness of the work of medical institutions, which is caused by the growth of requests and preferences of patients regarding the choice of a medical institution and the provision of services; the influence of digitalization on the quality of medical services and the work of medical institutions is substantiated. Attention is focused on the fact that a medical institution can become successful with an effective modern system of effective management. The main groups of factors that significantly affect the quality management process of a medical institution are characterized. The main advantages of the introduction of a technological approach to the practice of managing a medical institution are highlighted. The main mistakes in the work of the management staff of the medical institution are given. It has been proven that the effective functioning of medical institutions depends not only on the course of internal management processes, but also on the flexible adaptation of their activities to the changing environment. The essence of management methods in the current conditions of change is clarified. The main areas of improvement of the activity of medical institutions are proposed. The main mistakes of the manager that can reduce the effectiveness of management activities and the effectiveness of the restructuring of medical institutions have been identified. The expediency of creating an effective team of employees of a medical institution is substantiated.It has been proven that caring for quality patient care has a positive effect on the institution's profitability, which in turn requires the implementation of modern and effective methods of managing the quality of medical services. It has been proven that the quality of providing medical services is one of the fundamental problems in the functioning of a health care institution. In this connection, the main factors of ensuring quality management are highlighted and the main characteristics of the quality management system in the medical facility are given. Attention is focused on the fact that quality assurance is based on an integrated approach to quality at each stage of service provision. The article concludes that the creation of an effectively working medical institution is an important task today and requires significant work from the manager. Therefore, the demands of time and digital transformations should be on the agenda of all heads of medical institutions.